Economic optimum plant density of sweet corn does not increase root lodging incidence. Issue 5 (18th July 2021) - Williams, Martin; Hausman, Nicholas; Dhaliwal, Daljeet; Grift, Tony; Bohn, Martin
Abstract: Exploitation of plant density tolerance in sweet corn ( Zea mays L.), including the use of density‐tolerant hybrids at plant densities that optimize economic returns (hereafter called economic optimum plant density), has the potential to improve profitability. Multiple experimental approaches, including artificially created root lodging events in field trials and natural root lodging events in growers' fields, were used to determine if economic optimum plant densities, compared with current plant densities, increase incidence of root lodging in sweet corn. An artificially created root lodging experiment over multiple years showed the environment in which sweet corn is grown is far more important to the effects of root lodging than plant density. In trials with natural root lodging events, results showed commercial sweet corn hybrids differed greatly in their susceptibility to root lodging, with some cultivars tolerant across all plant densities. Across 16 experimental comparisons of sweet corn response to plant density where natural root lodging was observed, including seven environments and 11 commercial hybrids, there was no difference in root lodging between current and economic optimum plant densities. Factors other than plant density dominate the crop's potential for, and recovery from, root lodging in growers' fields, namely, the hybrid and the environment in which the crop is grown. Core Ideas: Optimizing economic plant density of density‐tolerant sweet corn improves profitability. Environment and hybrid have much greater effect on root lodging than plant density. Compared with current plant density, economic optimum plant density does not increase root lodging incidence.